Characterization of two strains of Pleurotus djamor native from Oaxaca, Mexico - León-Avendaño Hugo; Martínez-García Rosalva; Caballero Gutiérrez Pablo; Martínez-Carrera Daniel (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico the cultivation of Pleurotus spp., is based primarily on the use of strains of high quality and productivity of foreign origin (P. ostreatus), but there are native fungal resources not studied yet with better prospects locally. Were isolated and characterized strains of Pleurotus djamor native from the evergreen tropical forest in the municipality of Santiago Xanica, South highlands of Oaxaca, to know their attributes and the potential for introduction to crops in local substrates as a productive and food alternative. In September 2009, collected six fruiting of wild P. djamor in good condition (locally consumed species); two strains were isolated and purified (ITAO-3 and ITAO-6) and during 2010 were evaluated and compared with a commercial strain (CPC) on mycelial growth rate in culture media EMA, SIM and PDA, as well as its color and texture characteristics. Development was evaluated after inoculation on wheat grain as support mycelium. The results show that the strain ITAO-3 had higher mycelial growth rate in culture media PDA and EMA followed ITAO-6 which showed growth similarity to CPC. In tests of inoculum elaboration and mycelial invasion on wheat grain, ITAO-3 strain was optimal and shows qualities to be cultivated on different substrates.